Pengembangan Bahan Ajar Tematik Berbasis Kearifan Lokal Masyarakat Banten - Nana Sumarna; Nafan Tarihoran; Rhini Fatmasari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
Thematic learning in elementary schools requires instructional materials that are contextual and relevant to students’ daily lives. However, the materials currently used are generally national in scope and do not optimally incorporate local wisdom, resulting in less meaningful learning experiences. This study aims to develop thematic teaching materials based on the local wisdom of the Banten community and to examine their validity, practicality, and effectiveness. This study employed a Research and Development (R&D) method using the ADDIE model. The subjects of this study were 75 fifth-grade elementary school students. Data were collected through interviews, questionnaires, observations, and learning outcome tests. The results showed that the developed teaching materials significantly improved in quality, with validation scores increasing from 61% to 93%, indicating high validity. In addition, the materials were considered practical and effective in enhancing student engagement and learning outcomes. The findings imply that integrating local wisdom can foster more contextually relevant and meaningful learning.